Phylosohpy as art of measure in Plato - García Peña, Ignacio (Anales del Seminario de Historia de la Filosofía, 2007)
The given work analyses several aspects of the concept te’cnh in Plato´s philosophy. At the same time, it deals with his attempt of finding a type of behaviour which counts on the same features as arts and science, in other words, a behaviour based on rational principles that will enable us to act accurately and according to our principles. He followed the path of Socrates in the process of the search for such behaviour. The sophists were proud of teaching a certain political science that, to Plato, is an exclusive property of the philosopher who is acquainted with the intelligible forms and makes use of the right calculation and measure. According to him, these two would be the undeniable components of what we may define as the good and happy life of an individual.